Socio-Economic Grievances of Transgender Community in Pakistan: A Case Study of The Capital City, Islamabad - Kalhoro, Javed Ali; Khan, Mehmood (Annals of Human and Social Sciences, 2023)
Transgender community in Pakistan is one of the communities that has been side-lined from the social stream of the country. In this regard, there are numerous issues faced by transgender persons in Pakistan, to date. They often have to confront discrimination and violence, both from communities and the State of Pakistan. Such behaviour and the discriminatory social construction of Pakistani society against the community has led to a lack of quality education, unemployment, poor healthcare facilities and no legal recognition of thousands of Khawaja Saras, which ultimately results in devastating socio-economic conditions for transgender persons in Pakistan. Therefore, this study aimed to place a rational approach towards the transgender community of the federal capital city of Pakistan; Islamabad, to learn about their social and economic issues. This study also focuses on the Constitution of Pakistan with particular reference to the relevant articles within the constitution, which provide safety to each section of society. This study employs a qualitative study, followed by convenient sampling. For this study, we conducted open-ended interviews with the relevant stakeholders, along with secondary data sources.